Cost-effectiveness of the adjuvanted quadrivalent influenza vaccine in the elderly Belgian population - Sophie Marbaix; Nicolas Dauby; Joaquin Mould-Quevedo (Taylor & Francis Group, 2023)
Background Between 2015 and 2019, when 62% of Belgian adults aged ≥65 years were vaccinated with standard quadrivalent influenza vaccines, influenza caused an average of 3,905 hospitalizations and 347 premature deaths per year in older adults. The objective of the present analysis was to estimate the cost-effectiveness of the adjuvanted quadrivalent influenza vaccine (aQIV) compared to the standard (SD-QIV) and high-dose (HD-QIV) vaccines in elderly Belgians. Research Design and Methods The analysis was based on a static cost-effectiveness model that captured the evolution of patients infected with influenza and was customized with available national data. Results Vaccinating adults aged ≥65 years with aQIV instead of SD-QIV would decrease the number of hospitalizations by 530 and the number of deaths by 66 in the 2023-2024 influenza season. aQIV was cost-effective compared to SD-QIV with an incremental cost of €15,227/quality-adjusted life year (QALY). aQIV is cost-saving when compared to HD-QIV in the subgroup of institutionalized elderly adults who were granted reimbursement for this vaccine. Conclusion In a health care system striving to improve the prevention of infectious diseases, a cost-effective vaccine such as aQIV is a key asset to reduce the number of influenza-related hospitalizations and premature deaths in older adults.